An Analysis upon Various Influences of Social Media on Social Movements: Recent Prospect: Exploring the Impact of Social Media on Protests and Social Movements (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This report investigates the impact of social media upon social movement is designed to test the common hypothesis that Facebook, Twitter and other social media outlets had a significant impact on the outbreak of protests. These case studies focus on protesters’ use of social media, how social movement theory explains the role of social media, or other traditional methods of mobilization in these countries, governments’ use of social media to monitor and counter activists, and the role of social media in influencing international policy. The authors then develop two quantitative models, one to explore the correlation between protest activity and social media usage at the individual level, and the other to provide a forecast of the likelihood of social unrest given a certain set of country-level factors.